Виток позапарламентської опозиції та її роль у демократизації суспільства - Боєва, С. С.; Боева, С. С.; Boeva, S. (My University, 2011)
This article deals with the role of non-parliamentary opposition in the pro- cess of democratic transition. The topic is relevant in view of intensiﬁ cation of mass civil actions in Europe. In the article non-parliamentary structures are investigated as important actors of political and social transformations. On the basis of European political philosophy and practice it is proved that the non-parliamentary opposition is an indication of maturity of civil society, is a negative resistance of mazhoritarizm, and it deﬁ nes the process of democ- ratization of society and so on.
Боєва С. С. Витоки позапарламентської опозиції та її роль у демократизації суспільства / С. С. Боєва//Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 42. – С. -183 - 191.
Keywords: позапарламентська опозиція; демократизація суспільства; роль опозиції; демократичний транзит; соціальна трансформація; социальная трансформация; демократический транзит; роль опозиции; демократизация общества; внепарламентская опозиция; social Transformation; democratic transition; role opozitsii; democratization of society; extra-parliamentary oppositions